Development of Socio-Psychological Protection Mechanisms to Reduce Adolescents' Susceptibility to Religious Extremism - Mamatmurod ogli, Mamatrayimov Jumanazar (Indonesian Journal Publisher, 2025)
This study aims to identify and develop socio-psychological protection mechanisms that reduce adolescents' vulnerability to religious extremism. The research employs a mixed-method approach consisting of theoretical analysis, psychological surveys, interviews, and content analysis. It is grounded in the theories of identity development (Erikson), social-cognitive learning (Bandura), psychological resilience (Asmolov), and significance quest theory (Kruglanski). Findings indicate that adolescents are particularly susceptible to radical ideologies due to emotional instability, identity confusion, lack of critical thinking, and limited social support. Key protective factors identified include psychological resilience, family and peer support, critical media literacy, value-based education, and healthy identity formation. The study recommends the integration of psychoeducational programs, early screening, and multi-level collaboration among schools, families, and communities to effectively prevent youth radicalization.